Tro, moral og forandring i Indre Mission - Gundelach, Peter; Andersen, Peter B. (Religionsvidenskabeligt Tidsskrift, 2022)
ABSTRACT: The Danish Inner Mission (Home Mission) is a section of The Evangelical Lutheran Church in Denmark (ELCD), but it differs from the dominating church because it, like other evangelical groups, believes that the Bible as God’s written word is true in what it says and IM emphasizes orthodoxy, repentance, activism and attaches central importance the sacrifice of Jesus on the cross. Generational replacement and changes in socialization influence IM's friends, as the followers call themselves, to draw other religious and moral consequences from their faith than is common among the members of the Danish Evangelical Lutheran Church and in the general population. IM maintains that the organization stands religiously firm despite the changes in the surrounding world. Against this background, the article examines 1,765 responses to a unique survey among IM's friends regarding recruitment, beliefs, morality and religious socialization in IM. We find that the core elements in beliefs remain stable while generational changes create a gradual deterioration in the strict sexual-family values. This shows that religious changes within Inner Mission are not uni-directional in contrast to what is expected by general theories of religious changes such as secularization and individualization. RESUMÉ: Den danske folkekirkelige retning Indre Mission understreger ligesom andre evangelikale grupper en bibeltro kristendom der lægger vægt på ortodoksi, omvendelse og aktivisme, og som tillægger Jesu soningsdød på korset en central betydning. Ændringer i værdier mellem generationer samt socialisering leder IMs venner, som tilhængerne kalder sig selv, til at drage andre religiøse og moralske konsekvenser af deres tro end det er almindeligt blandt medlemmerne af den danske folkekirke og i befolkningen i øvrigt. IM fastholder at bevægelsen står fast til trods for forandringerne i den omgivende verden. Artiklen undersøger på baggrund 1.765 besvarelser på et unikt survey til IMs venner rekruttering, tro og moral og religiøs socialisering i IM. Vi finder en gradvis generationsmæssig udtynding af nogle moralske værdier, men samtidig medvirker familiemæssig socialisering fastholden af strikse trosforestillinger. Denne usamtidighed i forandringerne udfordrer de traditionelle, generelle teorier om lineær religiøs forandring.